2014
DOI: 10.1037/a0037661
|View full text |Cite
|
Sign up to set email alerts
|

Selection history modulates the effects of dual mechanisms on flanker interference.

Abstract: The limit of processing capacity and the effectiveness of top-down control are 2 mechanisms that underlie distractor interference in a flanker task. The current study investigates how the interblock selection history shaped by the target number and the predictability of distractor location may modulate the effects of these 2 mechanisms on flanker interference. Experiment 1 showed that the distractor compatibility effect was eliminated when the task array contained 4 or 5 identical targets, which reflected the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 88 publications
2
10
0
Order By: Relevance
“…These results showing that selection history modulates distractor processing are in line with a number of previous studies (e.g., Chen, 2008; Cosman & Vecera, 2013; Leber & Egeth, 2006; Müller, Geyer, Zehetleitner, & Krummenacher, 2009; Yeh, Lee, Chen, & Chen, 2014). Leber and Egeth (2006) demonstrated that their participants, who learned in the training phase to use one of two search modes to find a color-defined target, continued to use the same search mode to perform the task in the subsequent test phase even though the task could be performed with either search mode.…”
Section: Methodssupporting
confidence: 93%
“…These results showing that selection history modulates distractor processing are in line with a number of previous studies (e.g., Chen, 2008; Cosman & Vecera, 2013; Leber & Egeth, 2006; Müller, Geyer, Zehetleitner, & Krummenacher, 2009; Yeh, Lee, Chen, & Chen, 2014). Leber and Egeth (2006) demonstrated that their participants, who learned in the training phase to use one of two search modes to find a color-defined target, continued to use the same search mode to perform the task in the subsequent test phase even though the task could be performed with either search mode.…”
Section: Methodssupporting
confidence: 93%
“…Effects of selection history have also been reported in visual search studies (e.g., Chun & Jiang, 1998;Leber & Egeth, 2006;Yeh et al, 2014), including those in which the target was a singleton (e.g., Bravo & Nakayama, 1992;Chen & Cave, 2015;Leonard & Egeth, 2008;Maljkovic & Nakayama, 1994;Müller et al, 2003). The latter studies are particularly interesting because searching for a singleton can be accomplished easily via stimulus-driven processes due to its salience.…”
Section: Discussionmentioning
confidence: 88%
“…Although the deployment of a specific attentional control setting is traditionally thought to be influenced primarily by top-down factors such as the current selection goal and bottom-up factors such as the salience of the target relative to distractors, there is increasing evidence that past experience, or selection history, also plays an important role (see Awh et al, 2012, andKristjànsson &Campana, 2010, for reviews). Selection history has been found to affect performance immediately (e.g., Chen & Cave, 2015;Leonard & Egeth, 2008;Maljkovic & Nakayama, 1994), across different blocks of trials (e.g., Leber & Egeth, 2006;Yeh et al, 2014), and even after a week (e.g., Leber et al, 2009). In Maljkovic and Nakayama, participants searched for an oddcolored target among distractors of a homogeneous color.…”
Section: Introductionmentioning
confidence: 99%
“…An infrequently presented onset distractor leads to significant distraction processing while a frequently presented one does not (Cosman & Vecera, 2010), and both perceptual grouping and the salience of a target relative to the distractor and/or the other stimuli in a display affect the degree of distractor processing (Baylis & Driver, 1992;Biggs & Gibson, 2013;Biggs, Kreager, & Davoli, 2015;Eltiti, Wallas, & Fox, 2005;Yeh & Lin, 2013;Yeshurun & Marciano, 2013). These and other empirical findings Biggs & Gibson, 2010;Chen & Chan, 2007;Wilson et al, 2011;Yeh, Lee, Chen, & Chen, 2014 ), together with the conceptual and methodological issues raised by a number of researchers (see Benoni & Tsal, 2013;Giesbrecht, Sy, Bundesen, & Kyllingsbaek, 2014;and Murphy, Groeger, & Greene, 2016, for reviews), indicate that the simple principles of PLT do not fully capture the complex interactions among targets and nontargets in complex stimulus arrays. In this review we will focus primarily on behavioral studies that do not involve a secondary task.…”
Section: Perceptual Loadmentioning
confidence: 89%